Pengaruh Stres Kerja Berat Terhadap Kecenderungan Gangguan Mental Emosional Pada Staf Manajerial Perusahaan Penanaman Modal Asing - Azhariya, Rachmawati Ayu; Prihartono, Joedo; A Kusumawardhani, A Kusumawardhani (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2019)
Introduction: This study aims to assess the association of severe occupational stress among managerial staff with the tendency of mental emotional disorder. Methods: The study was conducted from March to May 2016 at a Foreign Cooperation in West Java with comparative cross-sectional method. Occupational stress was measured with Stress Diagnostic Survey (SDS), whilst the tendency of mental emotional disorder was assessed with Symptom Check List 90 (SCL 90). A hundred and five respondents were asked to fill out the SDS questionnaire. Furthermore, 30 respondents were randomly selected from each group of mild-moderate and severe occupational stress. Results: The prevalence of severe occupational stress on managerial staff is 35.2%. There was a significant association between severe occupational stress with the tendency of mental emotional disorder (OR 47; 95% CI 7.37-300.17; p less than sign 0.001). Components of occupational stressors which statistically significant with mental emotional disorder are the qualitative workload (OR 10.67; 95% CI 1.03-109.94; p 0.047) and career development (OR 10.83; 95% CI 1.03 -114.15; p 0.047). Education is an individual factor that statistically significant against the tendency of mental emotional disorder (OR 0.17; 95% CI 0.03 to 0.83; p 0.029). Conclusion: There was no significant relationship between work factors with the tendency of mental emotional disorder.